2002
DOI: 10.1186/1471-2407-2-32
|View full text |Cite
|
Sign up to set email alerts
|

The differentiation status of primary gonadal germ cell tumors correlates inversely with telomerase activity and the expression level of the gene encoding the catalytic subunit of telomerase

Abstract: Background: The activity of the ribonucleoprotein enzyme telomerase is detectable in germ, stem and tumor cells. One major component of telomerase is human telomerase reverse transcriptase (hTERT), which encodes the catalytic subunit of telomerase. Here we investigate the correlation of telomerase activity and hTERT gene expression and the differentiation status of primary testicular germ cell tumors (TGCT).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 42 publications
1
7
0
Order By: Relevance
“…SPRY4 responds to KIT inhibition by imatinib [396]. TERT and its transcription factor ATF7IP influence telomere maintenance (normally only active in germ cells) [397,398]. The TERT-CLPTM1L locus is a cancer-hotspot ( [149] for review) and CLPTM1L is involved in cisplatin sensitization [399].…”
Section: Environmental Risk Factorsmentioning
confidence: 99%
“…SPRY4 responds to KIT inhibition by imatinib [396]. TERT and its transcription factor ATF7IP influence telomere maintenance (normally only active in germ cells) [397,398]. The TERT-CLPTM1L locus is a cancer-hotspot ( [149] for review) and CLPTM1L is involved in cisplatin sensitization [399].…”
Section: Environmental Risk Factorsmentioning
confidence: 99%
“…, 2002b). Moreover, it has been observed that undifferentiated TGCTs (seminomas) exhibit the pattern of high TERT expression, high telomerase activity and long telomeres seen in normal testicular germ cells, while well‐differentiated TGCTs such as teratomas show minimal TERT expression and no telomerase activity (Schrader et al. , 2002a,b).…”
Section: Tgct Predisposition Loci Identified Via Genome‐wide Associatmentioning
confidence: 99%
“…Though TERT is expressed during embryonal development, it is usually absent in somatic cells (Greenberg et al ., ), and upregulation of TERT expression is one of the hallmarks of cancer (Jafri et al ., ). In TGCT, the expression of TERT and activity of telomerase activity are high in seminomas, while teratomas show intermediate expression of TERT (Schrader et al ., ). Jia et al .…”
Section: Telomerase Activitymentioning
confidence: 97%